High rate of durable remissions after treatment of newly diagnosed aggressive mantle-cell lymphoma with rituximab plus hyper-CVAD alternating with rituximab plus high-dose methotrexate and cytarabine - Romaguera, Jorge E; Fayad, Luis; Rodriguez, Maria A; Broglio, Kristine R; Hagemeister, Frederick B; Pro, Barbara; McLaughlin, Peter; Younes, Anas; Samaniego, Felipe; Goy, Andre; Sarris, Andreas H; Dang, Nam H; et al. (Journal of clinical oncology, 2005)
To determine the response, failure-free survival (FFS), and overall survival rates and toxicity of rituximab plus an intense chemotherapy regimen in patients with previously untreated aggressive mantle-cell lymphoma (MCL). This was a prospective phase II trial of rituximab plus fractionated cyclophosphamide, vincristine, doxorubicin, and dexamethasone (hyper-CVAD; considered one cycle) alternating every 21 days with rituximab plus high-dose methotrexate-cytarabine (considered one cycle) for a total of six to eight cycles. Of 97 assessable patients, 97% responded, and 87% achieved a complete response (CR) or unconfirmed CR. With a median follow-up time of 40 months, the 3-year FFS and overall survival rates were 64% and 82%, respectively, without a plateau in the curves. For the subgroup of patients < or = 65 years of age, the 3-year FFS rate was 73%. The principal toxicity was hematologic. Five patients died from acute toxicity. Four patients developed treatment-related myelodysplasia/acute myelogenous leukemia, and three patients died while in remission from MCL. A total of eight treatment-related deaths (8%) occurred. Rituximab plus hyper-CVAD alternating with rituximab plus high-dose methotrexate and cytarabine is effective in untreated aggressive MCL. Toxicity is significant but expected. Because of the shorter FFS concurrent with significant toxicity in patients more than 65 years of age, this regimen is not recommended as standard therapy for this age subgroup. Larger prospective randomized studies are needed to define the role of this regimen in the treatment of MCL patients compared with existing and new treatment modalities.